The Effect of Vitamin C Supplementation on Malondialdehyde Levels and Psychological Stress in Medical Students of Yarsi University, Class of 2022 - Sasmi Naria Fahm; Linda Weni (Green Publisher Indonesia, 2026)
This study addresses the high prevalence of psychological stress among medical students, which can trigger oxidative stress characterized by increased Malondialdehyde (MDA) levels. Vitamin C, as a potent antioxidant, is expected to reduce oxidative stress and improve psychological conditions. Therefore, this study aims to examine the effect of vitamin C supplementation on MDA levels and psychological stress among medical students of YARSI University class of 2022. This research employed a quantitative experimental design using a Randomized Controlled Trial (RCT) approach. A total of 36 respondents were divided into four groups receiving vitamin C doses of 500 mg, 1000 mg, 1500 mg, and a control group. Data were collected through laboratory analysis using ELISA for vitamin C and MDA levels, and psychological stress was measured using the DASS questionnaire before and after intervention. The results showed that vitamin C supplementation at a dose of 1000 mg significantly reduced MDA levels and increased vitamin C concentration, while 500 mg and 1500 mg doses showed no significant effect on MDA. All supplementation doses contributed to reducing psychological stress, with the most consistent effect observed at 1000 mg and 1500 mg. In conclusion, vitamin C supplementation, particularly at a dose of 1000 mg, is effective in reducing oxidative stress and psychological stress among medical students, indicating its potential as a supportive intervention for student health.